2019
DOI: 10.5194/isprs-archives-xlii-3-w6-579-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Landsat-8 and Sentinel-2 Data for Classification of Rabi Crops Over Karnataka, India

Abstract: Classification of crops is very important to study different growth stages and forecast yield. Remote sensing data plays a significant role in crop identification and condition assessment over a large spatial scale. Importance of Normalized Difference Indices (NDIs) along with surface reflectances of remotely sensed spectral bands have been evaluated for classification of eight types of Rabi crops utilizing the Landsat-8 and Sentinel-2 datasets and performances of both the satellites are compared. Landsat-8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…From the literature review, many researchers have reported that the texture of the image reduces the improved classification accuracy in optical satellite data. Some researchers have analyzed both the optical and Sentinel SAR satellite images [15], [16]. Also, they have reported that the small spectral differences between these two satellite images affect the classification accuracy, but the sentinel landuse classification has high classification accuracy for most of the landuse classes [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the literature review, many researchers have reported that the texture of the image reduces the improved classification accuracy in optical satellite data. Some researchers have analyzed both the optical and Sentinel SAR satellite images [15], [16]. Also, they have reported that the small spectral differences between these two satellite images affect the classification accuracy, but the sentinel landuse classification has high classification accuracy for most of the landuse classes [17].…”
Section: Literature Reviewmentioning
confidence: 99%